Preparation of activated carbon from asphalt and asphalt treated with polymers using microwave radiation - Khalid Owaid; Ahmed Hammadi (College of Education for Pure Sciences, 2013)
ABSTRACT The study included the use of  two path in the process of preparation.The first pathway included preparation of the AC from Baiji asphalt by an oxidation process done at 350 °C using 2% FeCl3 for 3hours, after that the resulting product was distillated normal and vacuum distillation, and then the resulted of vacuum distillation were  carbonized at a temperature of 400°C for  2hours and treated with KOH at various ratios ranging from (0.5:1) ,(1:1) and(2:1) (potassium hydroxide: carbonized materials) using microwave radiation at power of (90,180,270,360,450,540,630,720) watt and at periods ranging between (4,6,8,10,12,14,16,18,20) minutes. The second pathway involved the treatment of  Baiji asphalt with different percentages of polymers ranging between (5,10,15,20,25)% of poly ethylene, poly styrene and melamine formaldehyde resin (which are thermally craclced )  at a temperature of 170°C for 1 hour with 1% AlCl3 as a catalyst of this process , and the resulted product was carbonized at a temperature of 400°C for 2 hours with addition of KOH at a ratio of (2:1) (potassium hydroxide: carbonized materials ) with radiation energy of 630watt for 16 minutes. Many tests were conducted on the samples of the prepared activated carbon for the purpose of determining its effectiveness by measuring its adsorption ability of aqueous solutions of Iodine and methylene blue dye as well as some other measurements as density, ash content and humidity were evaluated, and as a practical application of the effectiveness of one sample of the prepared AC adsorption of the azo dye 1,4-di(2-amino 4-hydroxy phenyl azo)benzene (1,4HAAB)  was conducted from its aqueous solution and compared it with the commercial one sample and it was noticed from this study the effectiveness of this AC sample in the adsorption of this dye. It is found from this study that the process of preparing activated carbon using microwave radiation gave good samples regarding to the ability of adsorption and some samples were better than the commercial samples, further more; the process of preparation has reduced the time of reaction from several hours to few minutes as well as providing energy and this is very important in terms of economic feasibility of the process.